Optimization of non thermal plasma reactor performance for the decomposition of xylene - Nor Azmi, N. F. S. (Penerbit UTM Press, 2016)
Non Thermal Plasma (NTP) is an emerging method used for the decomposition of volatile organic compounds (VOCs). This research focuses on the optimization of NTP reactor performance for decomposition of xylene from wastewater using response surface methodology (RSM) by operating the NTP reactor at applied voltage of 12-15 kV, discharge gap of 2.0-3.0 cm and gas flow rate of 2.0-5.0 L/min. An optimum xylene removal efficiency of 81.98% was obtained at applied voltage 15kV, discharge gap 2.09cm and gas flow rate at 2.36 L/min. The experimental removal efficiencies and model predictions were in close agreement with an error of 0.63%.